Enamide Derivatives: Versatile Building Blocks for Total Synthesis - Courant, Thibaut; Dagousset, Guillaume; Masson, Géraldine (Synthesis, 2015)
Enamides and enecarbamates are versatile building blocks in organic synthesis. This review describes the development of enamide chemistry and the utility of the resulting products in the synthesis of a variety of important, biologically active molecules.1 Introduction2 Asymmetric Hydrogenation of Enamides3 Monofunctionalization of Enamide Derivatives3.1 Palladium-Catalyzed α-Functionalization of Enamide Derivatives3.2 Ruthenium-Catalyzed β-Functionalization of Enamide Derivatives4 Ionic Vicinal Difunctionalization of Enamide Derivatives4.1 Tandem Difunctionalization of Enamide Derivatives4.2 Cycloadditions4.2.1 [4+2] Cycloadditions4.2.2 [2+2] Cycloadditions4.2.3 Cyclopropanation of Enamides4.3 Other Pericyclic Reactions4.3.1 Electrocyclization Reactions4.3.2 Overman Rearrangement4.4 Platinum-Catalyzed Vicinal Difunctionalization of Enamide Derivatives5 Radical Vicinal Difunctionalization of Enamide Derivatives6 Oxidative Vicinal Difunctionalization of Enamide Derivatives7 N-Arylation of Enecarbamates8 Conclusion9 Ligand Glossary
Keywords: enamide; total synthesis; alkaloid; hydrogenation; functionalization